Genome-wide characterization and identification of cyclophilin genes associated with leaf rust resistance in bread wheat (Triticum aestivum L.) - Tyagi, Sandhya; Jha, Shailendra Kumar; Kumar, Anuj; Saripalli, Gautam; Bhurta, Ramesh; Hurali, Deepak T.; Sathee, Lekshmy; Mallick, Niharika; Mir, Reyazul Rouf; Chinnusamy, Viswanathan; Vinod, (Frontiers in Genetics, 2022)
Cyclophilins (CYPs) are a group of highly conserved proteins involved in host-pathogen interactions in diverse plant species. However, the role of CYPs during disease resistance in wheat remains largely elusive. In the present study, the systematic genome-wide survey revealed a set of 81 TaCYP genes from 3 subfamilies (GI, GII, and GIII) distributed on all 21 wheat chromosomes. The gene structures of TaCYP members were found to be highly variable, with 1-14 exons/introns and 15 conserved motifs. A network of miRNA targets with TaCYPs demonstrated that TaCYPs were targeted by multiple miRNAs and vice versa. Expression profiling was done in leaf rust susceptible Chinese Spring (CS) and the CS-Ae. umbellulata derived resistant IL "Transfer (TR). Three homoeologous TaCYP genes (TaCYP24, TaCYP31, and TaCYP36) showed high expression and three homoeologous TaCYP genes (TaCYP44, TaCYP49, and TaCYP54) showed low expression in TR relative to CS. Most of the other TaCYPs showed comparable expression changes (down- or upregulation) in both contrasting TR and CS. Expression of 16 TaCYPs showed significant association (P<0.05) with superoxide raical and hydrogen peroxide abundance, suggesting the role of TaCYPs in downstream signaling processes during wheat-leaf rust interaction. The differentially expressing TaCYPs may be potential targets for future validation using transgenic (overexpression, RNAi or CRISPR-CAS) approaches and for the development of leaf rust-resistant wheat genotypes.